Error Analysis of College Students’ English Application Letters at STMIK Sinar Nusantara - Saly Kurnia Octaviani; Arum Sari (International Journal of English Linguistics, Literature, and Education (IJELLE), 2021)
AbstractWriting as one of language aspects becomes the main language practice in each English class. Regarding to the college student task, writing English job application letter requires college students to provide the well-formed letter for job preparation. Therefore, understanding the errors of English sentence structure in college students’ job application letters can bring the suitable English grammar study for writing the formal letter. This research was conducted to find the errors on English job application letters written by college students in fourth semester at STMIK Sinar Nusantara. The respondents were selected as many as 30 students by using purposive random sampling technique. The collected data were taken from the respondents’ writings, English job application letter. The analysis used the algorithm of conducting error analysis proposed by Corder. In this research, students’ job application letters indicate omission with its 92 data or 35,35 % error, mis-formation with its 80 data or 30,80% error, mis-ordering with its 63 data or 24,23% error, and addition with its 25 data or 9,62% error. This research indicates that though the students had references of English job application letters from internet, they still had errors in writing own English sentences in formal form. Keywords: Error Analysis, English Error Analysis, English Application Letters, Job Application Letters, English Formal Letters